Tuning Organic Carbon Dioxide Absorbents for Carbonation and Decarbonation - Rajamanickam, Ramachandran (Sci Rep, 2015)
The reaction of carbon dioxide with a mixture of a superbase and alcohol affords a superbase alkylcarbonate salt via a process that can be reversed at elevated temperatures. To utilize the unique chemistry of superbases for carbon capture technology, it is essential to facilitate carbonation and decarbonation at desired temperatures in an easily controllable manner. Here, we demonstrate that the thermal stabilities of the alkylcarbonate salts of superbases in organic solutions can be tuned by adjusting the compositions of hydroxylic solvent and polar aprotic solvent mixtures, thereby enabling the best possible performances to be obtained from the various carbon dioxide capture agents based on these materials. The findings provides valuable insights into the design and optimization of organic carbon dioxide absorbents.